2021
DOI: 10.1021/acs.nanolett.1c00947
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Thermal and Electrical Properties of Sb2Te3/GeTe Superlattice Films

Abstract: Superlattice-like phase change memory (SL-PCM) promises lower switching current than conventional PCM based on Ge2Sb2Te5 (GST). However, a fundamental understanding of SL-PCM requires detailed characterization of the interfaces within such a SL. Here, we explore the electrical and thermal transport of SLs with Sb2Te3/GeTe alternating layers of various thicknesses. We find a ~3× reduction of the effective crossplane thermal conductivity of Sb2Te3/GeTe (4/1 nm/nm) SL compared to crystalline GST due to the therma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…This feature is typical for incongruent melting of alloy with non-eutectic composition and possibly a useful signature of cycle failures in PCM devices with antimony migration. [55] NanoDSC characterization of the melting peak is also important for novel phase-change materials including superlattice Sb 2 Te 3 /GeTe [12,13] and Ge 4 Sb 6 Te 7 . [56,57] GST can be completely evaporated after first melting without a capping layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature is typical for incongruent melting of alloy with non-eutectic composition and possibly a useful signature of cycle failures in PCM devices with antimony migration. [55] NanoDSC characterization of the melting peak is also important for novel phase-change materials including superlattice Sb 2 Te 3 /GeTe [12,13] and Ge 4 Sb 6 Te 7 . [56,57] GST can be completely evaporated after first melting without a capping layer.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Ge-Sb-Te ternary chalcogenides [7,8] used in PCM are located on the pseudobinary line between GeTe and Sb 2 Te 3 and have extraordinary properties including 1) metal-insulator transition in the crystalline phase, [9,10] 2) phase separation during incongruent melting, [11] 3) large density of ordered/disordered vacancies (>10%), [10] and 4) tunable thermal conductivity via van der Waals interfaces. [12,13] Among them, Ge 2 Sb 2 Te 5 (GST) has been intensively studied and commercialized [14] given its fast crystallization as a poor glass former, dramatic change of electrical/optical properties after switching, [15] and high stability in amorphous phase. However, the fundamental mechanism of GST crystallization remains mysterious in many aspects, such as whether it crystallizes from amorphous states and whether GST is a strong or fragile glass-forming liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work had suggested that Ge atom movement may be responsible for switching in similar superlattice PCM on rigid substrates ( 21 ). However, we have recently found that the superlattice has low cross-plane thermal conductivity and very high electrical anisotropy ( 35 ) owing to its numerous parallel vdW-like interfaces. Thus, we exploited these properties to conceive our design, which includes confinement of the superlattice PCM cell in a pore-like geometry on a substrate with ultralow thermal conductivity (the flexible PI).…”
mentioning
confidence: 99%
“…Recently, superlattice (SL) phase change materials with ultrathin alternating layers (e.g., TiTe 2 /Sb 2 Te 3 , GeTe/Sb 2 Te 3 , or GeSb 2 Te 4 /Sb 2 Te 3 ) have been reported to lower the switching current density ( J reset ), resistance drift coefficient ( v ), and switching time in PCM. , Low cross-plane thermal conductivity and high cross-plane electrical resistivity of the SL films generate electro-thermal confinement in SL-PCM, driving the energy-efficiency in such devices. , The electro-thermal properties of the SL materials stem from the van der Waals (vdW)-like interfaces within the SL, which have also been studied in other material systems; , the vdW-like interfaces are qualitatively similar but weaker than in covalently bonded SLs such as SiGe. Thus, SL interfaces, in particular their interface density and their intermixing (i.e., loss of vdW-like gaps, stacking faults, and disordering), can play a key role in the SL-PCM device performance.…”
mentioning
confidence: 99%
“…We measured the effective cross-plane thermal conductivity ( k eff ) of our superlattices (Figure f) with varying period thickness using a time domain thermoreflectance (TDTR) technique described in detail elsewhere. , Our measured k eff of the ST/GST superlattices decreases with increasing number of interfaces, that is, with decreasing period thickness from 16/14.4 nm/nm (4 interfaces) to 2/1.8 nm/nm (32 interfaces). A minimum k eff ≈ 0.33 ± 0.01 Wm −1 K −1 is measured for the 2/1.8 nm/nm stack.…”
mentioning
confidence: 99%